Normativité, grande santé et persévérance en son être - Pierre Roche (Perspectives Interdisciplinaires sur le Travail et la Santé)
What is health? How can it be approached in a positive way without merely identifying the hazards that it is likely to be subjected to in the course of the work activity? How can it be defended and, beyond that, consolidated in the workplace? For the author, nothing is more important than to escape a tradition which holds it as a state, that it be characterized by balance, adaptation, harmony, silence or even physical, mental and social well-being (WHO). In this work he introduces the concepts of normativity (Canguilhem), sound health (Nietzsche) and perseverance in one’s being (Spinoza). These concepts share the idea of considering health as a process and placing it on the ’power to act’ side. Concepts which, according to him, are defined in a line of thought likely to be the theoretical basis and axiological mainstay required by input-research endeavouring to rely on the active role of employees, their account and co-analysis of their work. In the last part of his article, the author seeks to identify the practical scope of such a definition. He also takes care to specify how input-research, that it helps support and promote in companies and institutions, opposes the recent "psychosocial risk prevention" issue.